Description of the Nest and Eggs of the Great-billed Seed-Finch (Sporophila maximiliani) - Medolago, Cesar A. B.; Ubaid, Flavio K. [UNESP]; Francisco, Mercival R.; Silveira, Luis F. (Wilson Ornithological Soc, 2016)
Seed-finches are Neotropical passerines highly specialized in the consumption of grass seeds. Most species are endangered because of the conversion of native grasslands into agricultural fields, and they are among the main victims of trapping for the illegal cage-bird trade in South America. The Great-billed Seed-Finch (Sporophila maximiliani) is very rare, with few records in the wild in the last 50 years. Here, we present the first descriptions for nest, eggs, and nesting habitat of the Great-billed Seed-Finch from Mato Grosso state, Brazil. We found the nests (two) on 18 December 2014 and on 8 January 2015. They were located in a seasonally flooded lowland area composed predominantly of herbaceous vegetation and sparse shrubs, mainly Curatella sp. Nests were built in 5 days, and only females participated in nest construction and incubation. Nests were cup-shaped made mainly of stems and tendrils of vines, and their measurements were: outside diameter (85.0, 93.0 mm); inside diameter (55.0, 60.0 mm); outside height (75.0, 83.0 mm) and inside high (40.0, 45.0 mm). Clutch sizes were two eggs. Eggs were grayish white, with light brown spots of variable sizes, and a smaller number of black blotches, more concentrated at the large end, measuring 203 16.9 mm (2.4 g), and 21.1 x 16.6 mm (2.9 g). Reintroductions into the wild have been recommended as a conservation strategy for this species, and knowledge on nesting sites and nest placement may be helpful for choosing areas for releases.
Keywords: breeding behavior; Neotropical birds; nesting biology; Oryzoborus